Case Report: Cotard's Syndrome in Anti-N-methyl D-aspartate (NMDA) Receptor (Anti-NMDAR) Encephalitis - Taib, Nur Iwana Abdul; Wahab, Suzaily; Khoo, Ching Soong; Tan, Hui Jan; Kamaruzaman, Lydia; Woon, Luke Sy-Cherng; Gan, Lydia Lay Yen (Frontiers in Psychiatry, 2022)
Cotard’s syndrome is uncommon psychopathology among patients with psychotic illnesses. Limited cases had been reported regarding the occurrence of this syndrome in anti-NMDAR encephalitis which itself is a relatively new disease that often presents with florid psychotic symptoms. This poses difficulties in differentiating it from a primary psychiatric illness. Late recognition of anti-NMDAR encephalitis can lead to death as it can progress to autonomic instability in its natural course of illness. We report a patient who first presented with psychotic symptoms with initial negative findings from baseline investigations. Further investigation revealed anti NMDAR antibodies in the cerebrospinal fluid. Prompt treatment was initiated and despite early poor response to the first-line treatment with the development of allergic reaction, our patient recovered completely after one month of hospitalization. This case report aims to highlight the importance of early detection of anti-NMDAR encephalitis and the possibility of uncommon psychopathology such as Cotard’s syndrome occurring in this disease.